INTRODUCTION OF STABILITY RATING OF BUSINESS ENTITIES IN THE REPUBLIC OF UZBEKISTAN AND ITS IMPACT ON THE BUSINESS ENVIRONMENT - Nutfulloev Tolib (Ecominds Press, 2025)
The article describes how the process of introducing the "Stability Rating of Business Entities" in the Republic of Uzbekistan took place and what results have been achieved so far. In addition, the indicators of the sustainability rating of business entities by region were analyzed econometrically with the volume of products and services created by business entities by region, and aspects of interdependence were studied. The results of the econometric analysis were verified by a series of tests. The obtained results were discussed and analyzed by the authors.
Keywords: Stability rating of business entities, sustainability, rating indicator, economy, regions, gross regional product, business entities, digital platforms, evaluation criteria, competition.